Los virus del frijol en Centroamérica. III. Razas del virus del mosaico común del frijol de El Salvador y Nicaragua - Gámez, R. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Common bean mosaic virus (CBMV) was isolated from beans (Phaseolus vulgaris) in different regions of El Salvador and Nicaragua. Characterization of the virus was based on host range, serological reactions, properties in sap and transmissibly by the aphid Myzus persicae. Reactions of a series of bean cultivars to infection by these isolates indicated that, in addition to the Costa Rican strain, three distinct and apparently new strains of CBMV were present.